Pattern Based Melody Matching Approach to Music Information Retrieval - Dara, Vikram; Mogalla, Shashi (Transactions on Engineering and Computing Sciences, 2017)
Digitization of music and advancements in information technology for sharing information on World Wide Web paved way for its availability in enormous quantities anywhere any time. Rather than retrieving annotated music in response to query given in terms of Metadata such as name of the composer/singer, genre etc modern researchers are challenged towards content based music information retrieval systems (CBMIR). CBMIR systems differ while representing the main melody either as a note sequence or as an analog acoustic signal; the note sequence representation is explored in this research work. Based on the observation that repeating patterns of the note sequences representing the main melody capture the essence of the music object, this research work developed a framework to investigate the feasibility and effectiveness of pattern based melody matching approach to music information retrieval. Experimentation is conducted on a real world dataset of musical objects belonging to South Indian classical music and the performance of the framework is estimated in terms of Mean Reciprocal Ranking.